Anomali Penerapan Klausul Bersyarat dalam Putusan Pengujian Undang-Undang terhadap Undang-Undang Dasar - Anang Sulistyono; Abdul Wahid; Mirin Primudyastutie (The Constitutional Court of the Republic of Indonesia, 2020)
In the implementation of constitutional review by the Constitutional Court, one of the dynamics occur is the emergence of conditionally constitutional unconstitutional decisions. Furthermore, the utilization of these types of decisions also has its dynamics, especially concerning the interpretation of conditional decisions. It can be indicated by the existence of anomalies decisions, which in the legal consideration, states that the norms reviewed are conditionally constitutional, but in its verdict, the norms are declared conditionally unconstitutional. Therefore, this paper aimed to comprehend the utilization of conditional decisions in constitutional review and to understand how is the anomaly in conditional clause implementation, as well as what Constitutional Court can do to prevent the anomalies to occur. Based on the analysis of conditional decision’s anomalies, there are at least three points that need to be pointed out. First, the anomalies increasingly show that conditionally constitutional and conditionally unconstitutional are substantially the same. Second, the use of conditionally constitutional clause as a ratio decidendi is considered to have no impact on the implementation of decisions. Third, the seven decisions analyzed further emphasized the Constitutional Court views that conditionally constitutional clause is deemed to be more effective in the implementation.